Urea and ammonium rejection by an aquaporin-based hollow fiber membrane. (December 2019) - Engelhardt, Sebastian; Vogel, Jörg; Duirk, Stephen E.; Moore, Francisco B.; Barton, Hazel A.
Abstract: Urea removal from aqueous solutions is a challenge in many field applications. Most available technologies are either energy intensive or complicated. Novel membrane-based processes such as forward osmosis (FO) present potentially desirable alternatives for energy efficient urea removal. Recently, aquaporin-based membranes (ABMs) gained attention due to their high water permeability and selectivity. In this study, a hollow fiber ABM module was investigated for both urea and ammonia/ammonium rejection under different conditions such as varying water recovery rates, initial feed solute concentrations, draw solution molarities and feed solution pH. The amount of water recovery significantly impacted urea rejection as a result of feed concentration increase and draw dilution over time. While only less than 37% of urea could be rejected for a water recovery rate of 80%, the rejection of urea for water recovery rates of 25% was above 82% when rejection was calculated via overall mass balance; however ammonium rejection at lower pH did exceed 90%, even under high water recovery rates. The increase of ammonium rejection at low pH is believed to be influenced by the decrease of bidirectional diffusion of sodium and ammonium cations favored by the less negative charge of carboxyl groups dominating the membrane surface's active layer. Since rejection for uncharged urea is rather poor, chemical processes that transform urea into ammonia/ammonium prior to the FO-step should be considered in future studies to improve rejection.